2013
DOI: 10.1002/minf.201300030
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Biodegradability of Chemical Compounds Using the Online CHEmical Modeling Environment (OCHEM)

Abstract: Biodegradability describes the capacity of substances to be mineralized by free‐living bacteria. It is a crucial property in estimating a compound’s long‐term impact on the environment. The ability to reliably predict biodegradability would reduce the need for laborious experimental testing. However, this endpoint is difficult to model due to unavailability or inconsistency of experimental data. Our approach makes use of the Online Chemical Modeling Environment (OCHEM) and its rich supply of machine learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…4,22,23,42 Final statistical results for the top-ranking models are summarized in Table 2. Below, we provide a detailed analysis of the steps, which were used to develop the model.…”
Section: Resultsmentioning
confidence: 99%
“…4,22,23,42 Final statistical results for the top-ranking models are summarized in Table 2. Below, we provide a detailed analysis of the steps, which were used to develop the model.…”
Section: Resultsmentioning
confidence: 99%
“…Obtained statistics for the EAT models with highest balanced accuracy corresponded or were slightly higher than for recently published models using similar data (Li and Gramatica, 2010b;Jensen et al, 2011;Papa et al, 2013;Zhang et al, 2013). The ASNN models are, however, difficult to interpret and thus as suggested by Vorberg and Tetko (2014), PLS models were used to increase our understanding on fundamental structural characteristics of EAT binders and non-binders. These models are described in detail in Section S5 and Table S4.…”
Section: Development Of Eat Modelsmentioning
confidence: 94%
“…Models with the ASNN method had the best quality and hence were used for further analysis. Studies have shown that the consensus model calculated out of individual models performed best [45,56,57]. An average consensus model was built using 10 QSAR models with the exception of that with spectrophore descriptors, due to its low performance.…”
Section: Qsar Modelsmentioning
confidence: 99%
“…A threshold value of 95% of compounds from the training set was used to determine the qualitative ADs of models. It is assumed that 5% of compounds outside the AD have little effect on the prediction confidence [56]. A Williams"s plot of the consensus model with CONSENSUS-STD as a distance to model is shown in Figure 2, and the AD defined above was used to warn users about unreliable predictions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%